A case report of diagnosis of cat-scratch disease using metagenomic next-generation sequencing - Zhou, Tao; Zheng, Yaqiu; Zhang, Huizi; Liu, Yongfang (Frontiers in Cellular and Infection Microbiology, 2024)
Cat-scratch disease (CSD) is an anthropozoonotic infection caused by Bartonella henselae, and it is one of the most common causes of lymph node infections in children and adolescents. B. henselae, belonging to the genus Bartonella, is a common human pathogen of human beings. CSD commonly develops as a result of cat scratches and bites or when injured skin comes into contact with cat saliva. The manifestation of CSD clinically differs for each patient based on their immune system. Individuals who have healthy immune systems generally manifest minimal clinical symptoms and do not necessitate any form of treatment. However, patients who have hypo-immunity require prompt medical attention due to the potential manifestation of severe symptoms that affect multiple systems of the body. Long latency and atypical clinical manifestations are characteristics of CSD. Bartonella isolation and identification are challenging procedures that require specialized equipment. There is no gold standard method for CSD diagnosis, and misdiagnosis and missed diagnosis rates are typically high. We present the case of a middle-aged male patient who developed fever, chills, anal distension, dizziness, and muscle pain for 10 days. The patient had a documented history of cat bites 1 month prior to the onset of symptoms. Following admission, he underwent an examination to determine superficial lymphadenopathy and hypoimmunity. Additionally, he had a fever during the disease. As the patient refused a needle biopsy of lymph nodes, metagenomic next-generation sequencing (mNGS) was employed and B. henselae was detected in the peripheral blood. The patient was diagnosed with CSD and treated with a combination of azithromycin and doxycycline. The fever symptoms were alleviated, and the patient was ultimately discharged. As a result of this case, we suggest that mNGS be used as a crucial supplementary diagnostic tool for individuals with compromised immune systems who may have CSD, especially when conventional diagnostic methods are inconclusive.